MODELING STUDY OF NATURAL AIR CIRCULATION IN HOTEL & RESORT BUILDING: Indonesia - Arief Rijaluddin (Universitas Majalengka, 2022)
The planning and design of a Hotel & Resort should be in accordance with the climate and location of the construction. In Indonesia, especially in areas that have cool air and are far from air pollution and noise pollution, they have a tropical climate, so Tropical Architecture is very suitable for planning and designing Hotels & Resorts, but it is possible to plan and design Hotels & Resorts with other architectural characteristics. Modeling studies can also be called modeling design and information about buildings, which is a field of science that examines development planning, development implementation, and maintaining and repairing if there is damage in a building. Activities from these fields of science are studying design drawings of houses, offices, buildings, and so on. In addition, this field of science does not only study building design, but this field of science will learn how to calculate the cost budget plan which is often referred to as RAB. Air circulation modeling has several sub-specifics, namely Planning Plan, building view, section view, Air Flow Scheme, and air circulation calculation. The building modeling method here uses an application called Autocad and SketchUp, then for the calculation of the natural air circulation using the ACPH (Hourly Air Exchange System) method. . Building 1 has a building area of ​​approximately 1486.7 M2 2 floors, building 2 has a building area of ​​461 M2 1 floor, and the hotel room area has a building area of ​​940.56 M2.